Pernikahan Endogami Pada Kalangan Perempuan Etnis Arab Di Indonesia - Muhammad Haidar Allam; Retno Hanggarani Ninin (Jurnal Kajian Ilmiah, 2023)
Until now, ethnic Arabs in Indonesia continue to grow and try to maintain their group identity. One of the traditions practiced is to maintain the continuity of descendants by marrying among fellow Arabs. Ethnic Arabs in Indonesia still adhere to the rule of endogamous marriage, which means they marry within their own ethnic group. This custom has created a strong sense of community and prejudice against other groups. Ethnic Arabs in Indonesia use paternal lineage or patrilineal rules in marriage, so men have the freedom to marry women from the Arab group or women from outside the Arab group because lineage is determined by the father. Women have the opposite fate from men, for women who do not undergo marriage are threatened with punishment. This research uses a qualitative method with a literature study approach. This research found that the practice of endogamous marriage among ethnic Arabs in Indonesia has significant impacts, especially for women. Although endogamous marriage is practiced to maintain the integrity of cultural and religious norms, this research shows that the practice has a negative impact on Arab women's health and well-being, as well as limiting their right to choose a life partner. In addition, endogamous marriages can also lead to stigmatization, discrimination and mental health issues for Arab women.